AUGMENTED REALITY: STUDY OF IMPLEMENTATION, IMPLICATIONS AND FUTURE DEVELOPMENT IN EDUCATION, RETAIL, MEDICAL AND MANUFACTURING SECTORS - tejas choudhary, sujata joshi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
There is an increasing implementation of advanced technologies to cater to the ever-changing needs of the consumer. Businesses are making use of these technologies to develop innovative services to attract more consumers.The purpose of this research paper is to understand the implementation of augmented reality technology in the services provided by businesses, implications on the business and improvements which can be done in future for provision of better service to the consumer. A case study approach has been adopted wherein various use cases related to Augmented Reality in education, retail, medical and manufacturing sectors are studied. This study will be useful for academicians, businesses to understand the use of augmented reality technology and develop new ways to increase its efficiency